Beyond Regionalism: The Politics of the Transboundary Haze Pollution in Southeast Asia - Ahmad Rizky M Umar (Institute of International Studies, 2021)
This article reviews two influential books by two Southeast Asian scholars that discuss the politics of transboundary haze pollution in Southeast Asia. In two excellent works addressing the transboundary haze pollution problem in the region, Paruedee Nguitragool and Helena Varkkey put forward two approaches to understand the failure to address transboundary haze pollution in the region with their own merits and limitations. On the one hand, Paruedee Nguitragool argues that the persistence of the transboundary haze pollution is linked to the regional dynamics in ASEAN and the ratification of the ASEAN Agreement on the Transboundary Haze Pollution (AATHP). On the other hand, Helena Varkkey points out a larger political-economic context that shapes the problem regionally, which relates to the palm oil plantation problem. I argue that, while both works have provided essential insights into the transboundary haze pollution in Southeast Asia, there are still spaces to discuss larger contexts underpinning the problem. I identify three issues that could be discussed in future research on the transboundary haze pollution, namely (1) the normative issue of protection and human rights to a safe, clean, and sustainable environment, (2) the local agency and dynamics in the forest fires and national haze problem, and (3) the nexus between transboundary haze pollution and regional climate change adaptations.